Enhancing Collaborative Teaching Through Developing Website-Based Learning Materials for Lecturers at Makassar Aviation Polytechnic - Sukarwoto; Moch. Rifai; Ahmad Fudholi; Rusman Rusman; Heru Prasetyo; Fachrurrazi Burhanuddin (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
This study aims to develop a website-based Learning Material Collaboration System (LMCS) for lecturers at Makassar Aviation Polytechnic. The system is designed to facilitate online collaboration in preparing teaching materials, ultimately enhancing the overall quality of learning using the waterfall method. Currently, teaching materials at the institution are independently prepared by the lecturers responsible for their respective courses, which results in non-standardized materials and limited collaboration between lecturers, practitioners, and cadets. The resulting materials are more comprehensive and sustainable through collaborative efforts in preparing teaching materials. The application requires lecturers to create an account, ensuring only authorized individuals can contribute and compile the teaching materials. This study proposes a collaborative platform that allows teaching materials to be prepared online to improve the effectiveness of learning and the quality of teaching materials. The LMCS application was tested to evaluate its reliability, efficiency, and effectiveness. The test results showed that the application effectively supported the collaboration of teaching materials, although some obstacles remained in managing cadet groups. Based on usability testing conducted with 10 participants, the application was user-friendly, with most testers successfully completing nearly all tasks. Analysis of the questionnaire using a Likert scale revealed positive user feedback, with the ease of use aspect scoring 82.6% and usability achieving a high score of 87.3%. Users felt that the application accelerated and facilitated the collaboration of teaching materials among lecturers and improved operational efficiency. However, for further development, training on the application and improvements to the user interface (UI/UX) are needed to ensure optimal use by all levels of users. The results of this study are expected to contribute to improving the quality of teaching materials and institutional accreditation at Makassar Aviation Polytechnic.